2018
DOI: 10.1097/nt.0000000000000302
|View full text |Cite
|
Sign up to set email alerts
|

Choline

Abstract: Choline has been recognized as an essential nutrient by the Food and Nutrition Board of the National Academies of Medicine since 1998. Its metabolites have structural, metabolic, and regulatory roles within the body. Humans can endogenously produce small amounts of choline via the hepatic phosphatidylethanolamine N -methyltransferase pathway. However, the nutrient must be consumed exogenously to prevent signs of deficiency. The Adequate Intake (AI) for choline was calculated at a time wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(66 citation statements)
references
References 55 publications
0
65
0
1
Order By: Relevance
“…A lack of choline in the maternal diet during critical periods of fetal development may cause lifelong changes in a child's brain structure and function, including the hippocampus. New evidence also suggests that sufficient maternal choline intake during pregnancy and lactation can have long-lasting beneficial neurocognitive effects on the offspring [29].…”
Section: Cholinementioning
confidence: 99%
“…A lack of choline in the maternal diet during critical periods of fetal development may cause lifelong changes in a child's brain structure and function, including the hippocampus. New evidence also suggests that sufficient maternal choline intake during pregnancy and lactation can have long-lasting beneficial neurocognitive effects on the offspring [29].…”
Section: Cholinementioning
confidence: 99%
“…The main dietary sources of the choline moiety, which is mostly present in food as lecithin (i.e., phosphatidylcholine), were reported to be eggs, liver, soybeans, and pork [11]. Although they are also present in numerous other foods [12], recent surveys in the USA indicated that choline may be underconsumed in specific populations (e.g., pregnant women and vegans) [13]. Based on the average observed choline intake in healthy European populations, a panel of the European Food Safety Authority set the adequate intake of choline at 400 mg/day [14].…”
Section: Introductionmentioning
confidence: 99%
“…The American Academy of Pediatrics identified several nutrients as essential for brain growth and development including choline, VitB6, and VitB12. The US Food and Drug Administration recommended 7 mg of choline per 100 Kcal as an optimal value for infants [32]. Despite this recommendation, some individuals do not meet their daily choline requirement and other individuals increase their intake above the recommended value.…”
Section: The Physiological Functions Of Choline and Other Methyl Donorsmentioning
confidence: 99%
“…AI varies from one individual to another and this variation is influenced by several factors such as age, sex, genetic and environmental factors [33][34][35]. For example, an elevated intake of choline is required for pregnant women to support fetal growth and development and improve neurocognitive functions of offspring later in life [12,32]. Premenopausal women require less intake of choline compared to postmenopausal women.…”
Section: The Physiological Functions Of Choline and Other Methyl Donorsmentioning
confidence: 99%
See 1 more Smart Citation